The Snail - Ngin, Yunxin (Nanyang Technological University, 2023)
The Snail is a 2D-animated short film about a boy who lives in a post-apocalyptic world, who sees a snail for the first time. The film follows the boy as he curiously follows, looks, and observes the snail. His observations end up being cut short by an airstrike siren, and he is forced to leave the area. The following report will reflect the process of producing this film, including pre-production preparation, production processes and problems, to post-production.